The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s00431-012-1813-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis delay in West syndrome: misdiagnosis and consequences

Abstract: West syndrome or infantile spasms is one of the most frequent epileptic syndromes in the first year of life. The clinical symptoms of infantile spasms are very different than any other type of seizure because of both the absence of paroxysmal motor phenomena (i.e., as in a convulsion) and the lack of significant duration of loss of consciousness (i.e., as in absence epilepsy). Infantile spasms may lead to misdiagnosis by pediatricians and other primary care providers. We assessed the missed diagnoses prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 19 publications
4
49
1
4
Order By: Relevance
“…Riikonen [4,5] reported that patients of WS with a favorable outcome had normal neurodevelopment before the onset of the spasms. Nearly all previous studies on this variable reported similar results [3,7,10,[21][22][23][24][25][26]. The presence of parental consanguinity and epilepsy in near relatives showed no significant effect on prognosis in this study.…”
Section: Neuro-developmental and Social Outcomessupporting
confidence: 83%
See 1 more Smart Citation
“…Riikonen [4,5] reported that patients of WS with a favorable outcome had normal neurodevelopment before the onset of the spasms. Nearly all previous studies on this variable reported similar results [3,7,10,[21][22][23][24][25][26]. The presence of parental consanguinity and epilepsy in near relatives showed no significant effect on prognosis in this study.…”
Section: Neuro-developmental and Social Outcomessupporting
confidence: 83%
“…Approximately 50% of patients with seizure onset before 12 months of age, excluding the neonatal period, suffer from WS characterized by infantile spasm (IS), psychomotor arrest or retardation, and hypsarrhythmia on electroencephalograms (EEG) [2][3][4]. Epileptic spasms most often show a temporal relationship with hypsarrhythmia, which is the typical interictal EEG activity in WS.…”
Section: Introductionmentioning
confidence: 99%
“…Так, S. Auvin и соавт. [9] сообщают о том, что пра-вильный диагноз не ставился примерно 80% детей (301 из 362 детей). В отечественной практике за-держка начала адекватной (в данном случае гормо-нальной) терапии, как правило, составляет несколь-ко месяцев.…”
Section: протоколы гормональной терапииunclassified
“…Onset of spasms is often associated with developmental arrest or regression. The primary goal of treatment is to stop the spasms early in the course of the disease in order to minimize the developmental delay . Up to 20% of patients fail to respond to current standard of care (SoC) with hormonal therapy, vigabatrin, or their combination …”
Section: Introductionmentioning
confidence: 99%